Comparison of field, greenhouse and detachedleaf evaluations of soybean germplasm for resistance to Phakopsora pachyrhizi - Twizeyimana, M.; Ojiambo, P.S.; Ikotun, T.; Paul, C.; Hartman, G.L.; Bandyopadhyay, Ranajit (Scientific Societies, 2007)
Fourteen soybean accessions and breeding lines were evaluated for resistance to soybean rust caused by the fungus Phakopsora pachyrhizi. Evaluations were conducted in replicated experiments in growth chambers using detached leaves and under greenhouse and field conditions. In growth-chamber experiments, inoculation of detached leaves with 1 × 106 sporesml resulted in a significantly (P < 0.0001) higher total number of pustules and spores per unit leaf area than inoculations with lower spore concentrations. Amending agar medium with plant hormones significantly (P < 0.0001) aided retention of green leaf color in detached leaves. Leaf pieces on a medium containing kinetin at 10 mgliter had 5% chlorosis at 18 days after plating compared with leaf pieces on media amended with all other plant hormones, which had higher levels of chlorosis. Leaf age significantly affected number of pustules (P = 0.0146) and number of spores per pustule (P = 0.0088), and 3- to 4-week-old leaves had a higher number of pustules and number of spores per pustule compared with leaves that were either 1 to 2 or 5 to 6 weeks old. In detached-leaf and greenhouse screening, plants were evaluated for days to lesion appearance, days to pustule formation, days to pustule eruption, lesion number, lesion diameter, lesion type, number of pustules, and spores per pustule in 1-cm2 leaf area. Plants also were evaluated for diseased leaf area (in greenhouse and field screening) and sporulation (in field screening) at growth stage R6. There were significant (P < 0.0001) differences among genotypes in their response to P. pachyrhizi infection in the detached-leaf, greenhouse, and field evaluations. Accessions PI 594538A, PI 417089A, and UG-5 had very low levels of disease compared with the susceptible checks and all other genotypes. Detached-leaf, greenhouse, and field results were comparable, and there were significant correlations between detached-leaf and greenhouse (absolute r = 0.79; P < 0.0001) and between detached-leaf and field resistance (absolute r = 0.83; P < 0.0001) across genotypes. The overall results show the utility of detached-leaf assay for screening soybean for rust resistance.